Huatanmaitong tablet alleviate cerebral ischemic reperfusion injury with hyperlipidaemia in rats by regulating OATPs/VEGF axis: Huatanmaitong tablet mitigates brain injury in hyperlipidemic rats - Sun, Shuangxi; Wang, Qi; Chen, Hongxia; Pan, Ruihuan (Cellular and Molecular Biology, 2023)
Stroke is the top priority pathogenesis of disability and death globally, affecting people worldwide. The presence of high levels of lipids in the blood has been confirmed as a vital factor of ischemic stroke. We aim to examine the effectiveness of Huatanmaitong tablet in hyperlipidemia rats that have experienced an ischemic stroke. We created a rat model of middle cerebral artery occlusion (MCAO) with hyperlipidemia as a basis. Following 8 weeks of high-fat diet, the model rats underwent MCAO surgery. Subsequently, the rats were administered huatanmaitong tablets and lipitor tablets as treatments. Therefore there are five groups, CONTROL, MCAO, hyperlipidemia (HLP), Huatanmaitong tablet (HTMTT) and Lipitor (LIPITOR) groups respective ly. To assess the efficacy of the medication, the serum lipid levels of rats were measured both prior to and following administration. Hematoxylin eosin staining was used to observe the alterations in the brain and liver structures within each group. VEGF and OATPs related factors were detected in brain, liver by using immunohistochemistry, Western blotting, and Quantitative PCR. After the model was established successfully, the infarct volume and behavioral scores of the model group, hyperlipidemia group, Huatan Maitong tablet group and Lipitor group had statistical differences (P<0.05). Blood lipid levels of rats were measured before and after treatment, and it was found that Huatanmaitong tablets effectively reduced these levels. Hematoxylin and eosin staining of the brain and liver showed that huatanmaitong tablets maintained the microstructure stability. Western blotting and real-time PCR revealed that Huatanmaitong tablets improved the expression level of organic anion transport (OATP1B1, OATP2B1) in rat tissues with ischemic stroke, enhancing the transmembrane transport of exogenous substances and maintaining homeostatic balance. Additionally, it down-regulated the expression of VEGF in various organs such as the brain, and liver, demonstrating the ability of Huatanmaitong tablets to remove phlegm, blood stasis, and promote circulation by regulating serum lipid levels, organic anion transport peptide, and VEGF in rats. The behavioral score of ischemic stroke rats can be improved and the neurological impairment symptoms of rats can be alleviated by Huatanmaitong tablet through the regulation of OATPS/VEGF axis.